Implementasi Kebijakan Koperasi Merah Putih dalam Mengurangi Ketimpangan Ekonomi di Provinsi Jawa Barat - Anisaah, Siti; Silitonga, Fredy wage Bimo; Putri, Nayla Larasati Arinda; Astuti, Bimbi Riris Tri; Shaqi, Rania Aisyah; Satispi, Evi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to analyze the implementation of the Merah Putih Cooperative Policy as stipulated in Presidential Instruction No. 9 of 2025 in an effort to reduce economic inequality and promote equitable development. The research method used is library research with secondary data sources in the form of scientific journal articles, policy reports, and books published in the last five years. Data was obtained through the Google Scholar and Garuda databases, then analyzed descriptively and analytically. The results of the study show that the Merah Putih Cooperative plays a role in expanding access to low-cost capital, strengthening the capacity of micro, small, and medium enterprises (MSMEs) through training, distribution of basic necessities, and integration with the People’s Business Credit (KUR) program with a financing allocation of up to Rp50 trillion. The implementation of this policy has contributed to a 5-7 percent increase in the province’s Gross Domestic Product (GDP), increased economic inclusion in rural areas, and an increase in cooperative member income. However, the implementation of this policy still faces obstacles in the form of low cooperative literacy, limited quality of managerial human resources, weak institutional governance, overlapping roles with Village-Owned Enterprises (BUMDes), and limited use of digital technology. The research findings indicate that the Merah Putih Cooperative Policy is quite effective in promoting community-based economic equality. Therefore, it is necessary to strengthen institutional capacity, accelerate the digitization of cooperatives, enhance inter-agency synergy, and conduct ongoing monitoring so that the implementation of this policy can be replicated nationally and aligned with the Sustainable Development Goals (SDGs).